The role of inquiry community in school public space - Espinoza-Díaz, Carlos; Arredondo-Ramírez, Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
One of the problems of modern society is the intentional abandonment of the community and of the public space. Customized technologies, consumerism, competitiveness and profit-driven private activities have taken over society’s shared interest. Education has set the same course, adopting public space practices which are appropriate to particular interests of those groups leading such projects. It is not concerning that community relationships become liquid and nonsensical for people, collectivities and the State itself. Nonetheless: What is the importance of public space in the school? How does inquiry community express itself in childhood’s public space? These questions intend to be the unifying thread of a dialog among inquiry community, public space, and childhood. Thereupon, we want to position the inquiry community as a starting point in the building up of free, democratic, broadminded, communal, and supportive citizens who are aware of their social and political role.